Correlation in endophytic fungi community diversity and bioactive compounds of Sophora alopecuroides - Ju, Mingxiu; Zhang, Qingchen; Wang, Ruotong; Yan, Siyuan; Li, Zhengnan; Li, Peng; Gu, Peiwen (Frontiers in Microbiology, 2022)
Sophora alopecuroides L. is a traditional Chinese medicine used for the treatment of several different disease states including bacillary dysentery and enteritis. But importantly, it also plays a role as an anti-tumor agent. That said, little is known about the role endophytes play regarding the clinically bioactive metabolites in S. alopecuroides. In order to explore the effects of endophytic fungi on the accumulation, quality, and the correlation in the content of the medicinal compounds, the structural diversity of endophytic fungi in S. alopecuroides were analyzed. The relationship between endophytes and quinolizidine alkaloids, housed within the seeds of S. alopecuroides, which were interpreted based on established methods of High-throughput Sequencing and High performance liquid chromatography. A total of 1,034,418 effective sequence reads and 257 operational taxonomic units (OTUs) were obtained from 33 samples which were sourced from 11 different sampling sites and further classified into 9 phyla, 20 classes, 45 orders, 85 families, and 118 genera. Ascomycota was found to be the dominant phylum of endophytic fungi in S. alopecuroides, with a relative abundance ranging from 60.85% to 98.30%. Alternaria, Cladosporium, Filobasidium, and an unidentified Ascomycota were the core-shared endophytes, accounting for 49.96%, 27.12%, 14.83%, and 7.88%, respectively. Correlation analysis showed that the Simpson’s Diversity Index of endophytic fungal community in S. alopecuroides was significantly positively correlated with the Oxymatrine content in different areas, while the Chao and Shannoneven index were significantly negatively correlated with Oxymatrine. The endophytic fungi of Alternaria were positively correlated with the content of Oxymatrine, Oxysophocarpine, and total quinolizidine alkaloids. This study has mastered the endophytic fungi resources of S. alopecuroides, explored potential functional endophytic fungi, and provided a scientific basis for using biological fertilization strategies to improve the quality of S. alopecuroides.